ANALISIS RANTAI NILAI JAGUNG JAGUNG PADA PT. SINAR TERANG MADANI MAKASSAR - Rindam Latief; Andi Dirpan; Faisal Jayadi (Jurnal Teknologi Industri Pertanian, 2023)
Value chain analysis is carried out to determine the percentage of added value of a product which has been process post-harvest treatments or turned into a new product in each step of marketing chain. This study aimed to determine the relationship between value chain actors and theirs added value of corn raw materials in feed production at PT. Sinar Terang Madani Makassar. Data obtained in this study were analyzed descriptively. The results showed that the value chain actors at PT. Sinar Terang Madani consisted of farmers, suppliers, manufacturers, customers, and distributors. Value chain actor with the highest profit was AM supplier, with a margin of Rp. 777/kg. Keywords: value chain analysis, corn, feed, supplier